Effects of Lactobacillus plantarum DAD 13, Inulin and Its Combination on Fecal Short Chain Fatty Acid Profile of Wistar Rats - Utami, Tyas (2010)
The aims of this works were the to study the effects of feeding L. plantarum Dad 13, inulin and both of them on fecal short chain fatty acids (SCFAs) in Wistar rats. After adaptation for 13 days with a standard diet, four groups of six Wistar rats were given different diets for 14 days i.e, standard diet as a control (CON), standard diet and L. plantarum Dad 13 (Dad13), inulin diet (lNU),and inulin diet with L. plantarum Dad 13 (lNU+Dad 13), and followed by feeding with standard diet again for 14 days. The results indicated that concentration SCFAs in rat fecal increased significantly with the feeding of inulin and combination of L. plantarum Dad 13 and inulin. Feeding of L. plantarum Dad 13 did not significantly effect the fecal SCFA concentration. Concentration of Fecal SCFA decreased after rats were fed with standard diet again.